Determing How Low Is the Performance of The Pavement Layers of Runway and Studying Maintenance. (Lattakia International Airport Is an example) - ديب عادل (Latakia University Journal -Engineering Sciences Series, 2022)
The airports sector is concerned with the management, operation and maintenance of airports to ensure the smoothness of passenger and aircraft traffic and to ensure the security and safety of air operations, in addition to developing commercial services, to bring them to global best practices, for the development of the air transport market, which helps to develop financial resources from its navigational and non-navigational sources. Airport is the take-off and arrival facility for passenger or cargo aircraft, it is located on flat ground containing routes, facilities and services for the movement of aircraft, in addition to providing fuel and maintenance, the runway must therefore feature special specifications commensurate with the size and type of aircraft using the airport. Runway are supplied by high flexible factors of pavement layers to be able to resist the loads which they expose to and this because of the repeated taking off and landing of aircrafts. Because of the frequent loads and climate conditions , flexible asphalt layers as well as solid concrete pavement layers expose for cracks and distortions which causes allow performance of the pavement layers and this demands taking essential requirements for raising the performance in order to be able to do its role well , and also putting a methodology to develop the performance by raising the classification number of the runway , so that they can receive the high loads aircrafts during the investment period of the airport . After conducting field and laboratory investigations for airport pavement layers, studies have found the runway of the airport needs more strength in order to raise its performance level to be able to receive all kinds of civil aircrafts in the reconstruction stage of our country.